Clutch‐size variation in Western Palaearctic secondary hole‐nesting passerine birds in relation to nest box design. Issue 4 (5th March 2014) - Møller, Anders Pape; Adriaensen, Frank; Artemyev, Alexandr; Bańbura, Jerzy; Barba, Emilio; Biard, Clotilde; Blondel, Jacques; Bouslama, Zihad; Bouvier, Jean‐Charles; Camprodon, Jordi; Cecere, Francesco; Chaine, Alexis; et al.
Summary Secondary hole‐nesting birds that do not construct nest holes themselves and hence regularly breed in nest boxes constitute important model systems for field studies in many biological disciplines with hundreds of scientists and amateurs involved. Those research groups are spread over wide geographic areas that experience considerable variation in environmental conditions, and researchers provide nest boxes of varying designs that may inadvertently introduce spatial and temporal variation in reproductive parameters. We quantified the relationship between mean clutch size and nest box size and material after controlling for a range of environmental variables in four of the most widely used model species in the Western Palaearctic: great tit Parus major, blue tit Cyanistes caeruleus, pied flycatcher Ficedula hypoleuca and collared flycatcher F. albicollis from 365 populations and 79 610 clutches. Nest floor area and nest box material varied non‐randomly across latitudes and longitudes, showing that scientists did not adopt a random box design. Clutch size increased with nest floor area in great tits, but not in blue tits and flycatchers. Clutch size of blue tits was larger in wooden than in concrete nest boxes. These findings demonstrate that the size of nest boxes and material used to construct nest boxes can differentially affect clutch size in different species. The findings also suggest that the nest box design may affect not only focal species, but also indirectly other species through the effects of nest box design on productivity and therefore potentially population density and hence interspecific competition.